Characteristics of elite swim turn performances - Mason, B. R.; Sacilotto, G.; Hazrati, P.; Mackintosh, C. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
It is generally undisputed that the turn is of paramount importance in distance and middle distance competitive swimming. Accordingly, there is a need to identifythe value of those parameters in the turn that are typical of international elite performance. This will be of vital importance in coaching, to assist swimmers to improve their performance in this aspect of competition. Using the Wetplate analysis system, many elite international swimmers were analysed performing a turn. Selected parameters for elite freestyle, butterfly, backstroke and breaststroke swimming in both genders, that represented the superior turners in each group, were analysed to identify a value for these parameters. A Pearson product moment correlation statistic was also performed on the data to identify those parameters that were of most significant interest in performance enhancement.